Етапи побудови національної геодезичної системи відліку в Україні - Заєць, І. (Видавництво Львівської політехніки, 2012)
Рассмотрены основные этапы построения в Украине национальной геодезической системы отсчета – государственной референцной системы координат. The main stages of construction in Ukraine national geodetic reference system – state reference system of coordinates.